Memória social das lutas pela moradia nas narrativas dos moradores da Vila União dos Operários - Canoas/RS - Fiorotti, Ivo (2015)
The present paper investigates – in the field of social memory and sociology - how the dwellers from Vila União dos Operários give account of the social movement struggle for access to housing and mobilizations for better habitation conditions which occurred between 1980 and 2014. They are used categories of sociological analysis such as social actor, social power, social exclusion, resistance and collective identity to understand the dynamics of this social movement. In theoretical field of social memory, the framing concepts of memory, organizing memories, factual memories, social identity and working memory are the main categories that lead this investigation. Related, those categories modulate the Hypothesis that the memories which abundantly populate the stories of those residentes are enchored in facts, events and ongoings which allow to understand the dynamics of this social movement. The memories produced by the speech of current dwellers are leaded and confronted with data from primary source documents collected from the community and their social organizations, among others, the Associação de Moradores da Vila União dos Operários – AMVUO and the Associação da Horta Comunitária União dos Operários – HOCOUNO. The results from this paper, in particular, the detailed reconstruction of this social movement anchored in the memories of residents as social actors and the production of a visual display with 10 banners using photos and documents of its main events and happenings, intend to be a contribution to the actions of cultural languages developed at Ponto de Cultura of HOCOUNO, in particular of drawing, photographic, music, video and theater.